2003
DOI: 10.1590/s0085-56262003000200017
|View full text |Cite
|
Sign up to set email alerts
|

Phlebotomines (Diptera, Psychodidae) in caves of the Serra da Bodoquena, Mato Grosso do Sul State, Brazil

Abstract: ABSTRACT. The present paper deals with the phlebotomine species captured during the period from January 1998 to June 2000 in 12 caves located in the Serra da Bodoquena, situated in the south central region of Mato Grosso do Sul State, Brazil. Three of the caves are situated further north (in Bodoquena county), seven in the central area (Bonito county) and two in the south (Jardim county). These last two caves and three of those in Bonito are located at the west side of the ridge. Eighteen species of phlebotomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
1
10

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 17 publications
5
45
1
10
Order By: Relevance
“…60.0 insects/trap in preserved and degraded areas) (Azevedo et al 2002). It is also much inferior to that obtained in the 12 caves sampled on the Serra da Bodoquena (62.8 insects/trap) (Galati et al 2003a). …”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…60.0 insects/trap in preserved and degraded areas) (Azevedo et al 2002). It is also much inferior to that obtained in the 12 caves sampled on the Serra da Bodoquena (62.8 insects/trap) (Galati et al 2003a). …”
Section: Discussionmentioning
confidence: 65%
“…The females captured were dissected for the investigation of natural infection by flagellates as described by Galati et al (2003a). When natural infection by flagellates was observed, the liquid containing the digestive tract was aspirated from the slide and inoculated into the hind legs of a hamster and also into NNN (Neal, Novy, and Nicole) medium with the liquid phase consisting of BHI (bovine brain, heart infusion) plus penicillin 1000 IU/ml and streptomycin sulfate 100 µg/ml.…”
Section: Points Of Capturementioning
confidence: 99%
See 1 more Smart Citation
“…Part of the data herein gathered were compiled from the literature, including publications such as the faunistic inventories , Pinto da Rocha 1995, Pintoda-Rocha & Sossegolo 2001, Galati et al 2003, Costa-Jr. 2004, Eriksson & Gonçalves 2010 and taxonomy-oriented works (Trajano et al 2000, Andrade et al 2001, Mahnert 2001, Labruna & Venzal 2009, Pires-Vanin 2012, in addition to unpublished dissertations (Moracchioli 2002, Cordeiro 2008 and grey literature (Godoy 1986. Original data came from collections by several speleobiologists in different occasions, including field courses, and more detailed identifications of material cited in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…A rich variety of sandfly species in different ecotopes has been identified in several ecological studies conducted in this state. These studies have indicated new species or have reinforced the role that some of them play in the transmission of leishmaniasis to the population of different municipalities, contributing to current understanding of the epidemiology of these diseases in the state [1][2][3][4][5][6] .…”
Section: Sand Fly Captures With Disney Traps In Area Of Occurrence Ofmentioning
confidence: 99%